Anthelmintic Efficacy of Polyherbal Formulation and Fenbendazole in Strongyle Infected Calves - Mishra, Akanksha; Bagherwal, Rajendra K; Mehta, Hemant K; Maheshwari, Pawan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted on strongyle infected cow calves  from organized and unorganized cattle farms located in and around Mhow (Indore, India) to assess the efficacy of polyherbal formulation (A mixture of Azadirchta indica, Momordica charantia, Allium cepa, Allium sativum, Brassica nigra, Musa paradisiaca, Cuminum cyminum, Curcuma longa and Piper nigrum)  and fenbendazole in strongyle infected calves. Total 12 infected calves (>500 EPG of strongyle) were randomly categorized in 2 groups of 6 calves in each. Group A was administered with polyherbal formulation, and Group B with fenbendazole. In the present study anthelmintic efficacy of polyherbal formulation and fenbendazole were evaluated by faecal egg per gram (EPG) of strongyle and haemato-biochemical parameters. The pre-treatment mean EPG in both treated group were reduced significantly (p
Keywords: Cow calves; Fenbendazole; Polyherbal formulation; Strongyle infection